Fungicide-driven evolution and molecular basis of multidrug resistance in field populations of the grey mould fungus Botrytis cinerea. - Matthias Kretschmer; Michaela Leroch; Andreas Mosbach; Anne-Sophie Walker; Sabine Fillinger; Dennis Mernke; Henk-Jan Schoonbeek; Jean-Marc Pradier; Pierre Leroux; Maarten A De Waard; Matthias Hahn (PLoS Pathogens)
The grey mould fungus Botrytis cinerea causes losses of commercially important fruits, vegetables and ornamentals worldwide. Fungicide treatments are effective for disease control, but bear the risk of resistance development. The major resistance mechanism in fungi is target protein modification resulting in reduced drug binding. Multiple drug resistance (MDR) caused by increased efflux activity is common in human pathogenic microbes, but rarely described for plant pathogens. Annual monitoring for fungicide resistance in field isolates from fungicide-treated vineyards in France and Germany revealed a rapidly increasing appearance of B. cinerea field populations with three distinct MDR phenotypes. All MDR strains showed increased fungicide efflux activity and overexpression of efflux transporter genes. Similar to clinical MDR isolates of Candida yeasts that are due to transcription factor mutations, all MDR1 strains were shown to harbor activating mutations in a transcription factor (Mrr1) that controls the gene encoding ABC transporter AtrB. MDR2 strains had undergone a unique rearrangement in the promoter region of the major facilitator superfamily transporter gene mfsM2, induced by insertion of a retrotransposon-derived sequence. MDR2 strains carrying the same rearranged mfsM2 allele have probably migrated from French to German wine-growing regions. The roles of atrB, mrr1 and mfsM2 were proven by the phenotypes of knock-out and overexpression mutants. As confirmed by sexual crosses, combinations of mrr1 and mfsM2 mutations lead to MDR3 strains with higher broad-spectrum resistance. An MDR3 strain was shown in field experiments to be selected against sensitive strains by fungicide treatments. Our data document for the first time the rising prevalence, spread and molecular basis of MDR populations in a major plant pathogen in agricultural environments. These populations will increase the risk of grey mould rot and hamper the effectiveness of current strategies for fungicide resistance management.